An alternative view to assessing antifragility in an organisation: A case study in a manufacturing SME. Issue 1 (2015) - Kennon, Denzil; Schutte, Corné S.L.; Lutters, Eric
Abstract In complex adaptive systems, antifragility designates the positive sensitivity to volatility, caused by (exceptional or 'black swan') external stressors that intervene with the intended functionality of these systems. System Engineers can purposefully employ the concept antifragility to engender better systems. Prerequisite for this is the ability to adequately assess system changes and especially system improvements as the consequence of stressors. Albeit antifragility measurements do exist, their practicality is limited. This publication proposes a novel approach for antifragility measurement. A case study on a manufacturing SME depicts the antifragile spectrum rating of an SME to test the effects of system changes.